Determining effects of nitrate, arginine, and ferrous on antibiotic recalcitrance of clinical strains of Pseudomonas aeruginosa in biofilm-inspired alginate encapsulates - Fereshteh Jabalameli; Mohammad Emaneini; Reza Beigverdi; Shahnaz Halimi; Maryam Siroosi (BMC, 2023)
Abstract Background Biofilms play a role in recalcitrance and treatability of bacterial infections, but majority of known antibiotic resistance mechanisms are biofilm-independent. Biofilms of Pseudomonas aeruginosa, especially in cystic fibrosis patients infected with the alginate producing strains in their lungs, are hard to treat. Changes in growth-related bacterial metabolism in biofilm affect their antibiotic recalcitrance which could be considered for new therapies designed based on these changes. In this study, effects of nitrate, arginine, and ferrous were investigated on antibiotic recalcitrance in alginate-encapsulated P. aeruginosa strains isolated from cystic fibrosis patients in the presence of amikacin, tobramycin, and ciprofloxacin. Also, expression of an efflux pump gene, mexY, was analyzed in selected strains in the presence of amikacin and ferrous. Methods Clinical P. aeruginosa strains were isolated from cystic fibrosis patients and minimum inhibitory concentration of amikacin, tobramycin, and ciprofloxacin was determined against all the strains. For each antibiotic, a susceptible and a resistant or an intermediate-resistant strain were selected, encapsulated into alginate beads, and subjected to minimal biofilm eradication concentration (MBEC) test. After determining MBECs, sub-MBEC concentrations (antibiotics at concentrations one level below the determined MBEC) for each antibiotic were selected and used to study the effects of nitrate, arginine, and ferrous on antibiotic recalcitrance of encapsulated strains. Effects of ferrous and amikacin on expression of the efflux pump gene, mexY, was studied on amikacin sensitive and intermediate-resistant strains. One-way ANOVA and t test were used as the statistical tests. Results According to the results, the supplements had a dose-related effect on decreasing the number of viable cells; maximal effect was noted with ferrous, as ferrous supplementation significantly increased biofilm susceptibility to both ciprofloxacin and amikacin in all strains, and to tobramycin in a resistant strain. Also, treating an amikacin-intermediate strain with amikacin increased the expression of mexY gene, which has a role in P. aeruginosa antibiotic recalcitrance, while treating the same strain with ferrous and amikacin significantly decreased the expression of mexY gene, which was a promising result. Conclusions Our results support the possibility of using ferrous and arginine as an adjuvant to enhance the efficacy of conventional antimicrobial therapy of P. aeruginosa infections.